2019
DOI: 10.1074/jbc.ra119.008005
|View full text |Cite
|
Sign up to set email alerts
|

The phytochemical bergenin as an adjunct immunotherapy for tuberculosis in mice

Abstract: The widespread availability and use of modern synthetic therapeutic agents have led to a massive decline in ethnomedical therapies. However, these synthetic agents often possess toxicity leading to various adverse effects. For instance, anti-tubercular treatment (ATT) is toxic, lengthy, and severely impairs host immunity, resulting in posttreatment vulnerability to reinfection and reactivation of tuberculosis (TB). Incomplete ATT enhances the risk for the generation of multidrug-or extensively drug-resistant (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 39 publications
0
25
0
1
Order By: Relevance
“…Bergenin is the C-glucoside of 4- O -methyl gallic acid and can be found in several medicinal plants, including Bergenia crassifolia and Corylopsis spicata ( Liang et al, 2017 ). Bergenin has been reported to have multiple biological activities, including antiarthritic ( Jain et al, 2014 ; Singh et al, 2017 ), immunomodulatory ( Wang et al, 2017 ; Kumar et al, 2019 ), antidiabetic ( Veerapur et al, 2012 ), osteogenic ( Hou et al, 2019 ), neuroprotective ( Barai et al, 2019 ; Ji et al, 2019 ), and wound-healing effects ( Mukherjee et al, 2013 ). Wang et al (2017) showed that bergenin attenuated colitis by activating the peroxisome proliferator-activated receptor (PPAR) γ.…”
Section: Introductionmentioning
confidence: 99%
“…Bergenin is the C-glucoside of 4- O -methyl gallic acid and can be found in several medicinal plants, including Bergenia crassifolia and Corylopsis spicata ( Liang et al, 2017 ). Bergenin has been reported to have multiple biological activities, including antiarthritic ( Jain et al, 2014 ; Singh et al, 2017 ), immunomodulatory ( Wang et al, 2017 ; Kumar et al, 2019 ), antidiabetic ( Veerapur et al, 2012 ), osteogenic ( Hou et al, 2019 ), neuroprotective ( Barai et al, 2019 ; Ji et al, 2019 ), and wound-healing effects ( Mukherjee et al, 2013 ). Wang et al (2017) showed that bergenin attenuated colitis by activating the peroxisome proliferator-activated receptor (PPAR) γ.…”
Section: Introductionmentioning
confidence: 99%
“…To date the evidence is limited that any host-targeting agent reproducibly reduces CFU of Mtb in otherwise genetically and pharmacologically unmanipulated animals infected with virulent Mtb when the HDT is administered after the onset of disease and as the sole intervention. The current portfolio of candidates for HDT of TB [ 4 7 ] includes candidates that were nominated based on treating mice infected with mycobacteria of a less virulent form than wild type Mtb [ 8 , 9 ], treating before the onset of disease [ 8 , 10 ], treating after knock out of a key element of immunity [ 11 ], or dosing with another agent that deviates the immune response [ 11 ], while others are effective against some Mtb strains and not others [ 12 ]. In some cases, the reduction in Mtb CFU was significant only after censoring some results [ 13 ], amounted to only ~0.2 log 10 [ 14 , 15 ], was reported from single experiments [ 13 , 15 ], or was not independently reproducible [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, they found that bergenin reduces the immune impairment of TB and thereby clears the bacteria fast in combination therapy with INH and reduces the bacterial burden more than 4 log in compared to 1 log reduction achieved by either INH or bergenin individually (Kumar et al . 2019). Moreover, bergenin also reverts the activation‐induced cell death of TB‐antigen‐specific T cells by isoniazid and provides the animals’ long‐term host protective immune response, which might be helpful for the development of herd immunity (Kumar et al .…”
Section: Ethnomedicinal Plants Of India and Their Key Bioactive Molecules On Tb Managementmentioning
confidence: 99%
“…Moreover, bergenin also reverts the activation‐induced cell death of TB‐antigen‐specific T cells by isoniazid and provides the animals’ long‐term host protective immune response, which might be helpful for the development of herd immunity (Kumar et al . 2019). Therefore, from all the ethnomedicinal work on S. robusta , it is proved that bergenin one of the bioactive molecules could be used as an immunomodulatory adjunct therapy with normal conventional TB treatment (Fig.…”
Section: Ethnomedicinal Plants Of India and Their Key Bioactive Molecules On Tb Managementmentioning
confidence: 99%